COMPARISON OF CVD RISK ASSESSMENT VIA QRISK®2 VS REYNOLDS RISK SCORE IN INFLAMMATORY JOINT DISEASES - Fozia Fatima,; Farzana Hakim,; Umer Ul Haq,; Muhammad Mehtab Shah,; Fakhara Saba Zeb,; Muhammad Iqbal Qasim,; Shahbaz Ali Khan,; Amer Fakhar,; Muhammad Adnan Manzar, (Journal of Ayub Medical College Abbottabad, 2022)
Background: The risk of cardiovascular disease in patients with inflammatory joint diseases is very high and rheumatologists need to screen their patients for this risk. A number of screening tools have been used in this patient population. Objective was to compare the cardiovascular risk assessment in patients with inflammatory joint diseases using QRISK®2 and Reynolds Risk Score. Methods: Four hundred and one patients with inflammatory joint diseases were enrolled via consecutive non-probability sampling. Their future cardiovascular disease risk was calculated via the QRISK®2 and Reynolds Risk Scores. The resulting scores were analyzed for any correlation. Results: There was no significant correlation between the scores obtain via both risk assessment tools (p>0.05).